Cultural Integration and Hybridization at the United States-Mexico Borderlands - Dear, Michael; Burridge, Andrew (Cahiers de géographie du Québec, 2005)
AbstractCultural hybridity is a relatively neglected issue in globalization studies. The term refers to the production of novel cultural forms and practices through the merging of previously separate antecedents. Hybridization is different from integration, in which interdependencies develop while the antecedents remain unaltered. Recent evidence from the United States-Mexico borderlands reveals several forms of integration and hybridization, including large-scale population migration, economic integration, adjustments in law and politics, cultural mixing, and transformations in identity. Although trends toward cultural integration and hybridity are not always positive, such postborder tendencies are regarded as cause for optimism regarding the relations between Mexico and the United States.